Legal Protection for Women Divorced Outside the Court in Indonesian Law - Sinaga, Risa Putri; Zurnetti, Aria; Yasniwati, Yasniwati (Faculty of Law, Andalas University, 2025)
This article investigates the legal protection of divorced women outside the court from civil and criminal law perspectives. Using a qualitative empirical juridical approach, this study was conducted in Nagari Pasar Tapan, a subdistrict in Pesisir Selatan Regency, West Sumatra, where extra-judicial divorces are still prevalent due to factors such as limited legal literacy, economic hardship, and the lack of access to judicial institutions. The findings indicate that extra-judicial divorce not only causes legal uncertainty in terms of marital status but also deprives women of their post-divorce rights, including maintenance, shared asset division, and child custody. Moreover, informal divorces often expose women to criminal accusations, such as polyandry, as a result of subsequent marriages not recognized by the state. This study emphasizes the importance of legal reforms, including increased awareness of divorce procedures, access to legal aid, and the strategic role of notaries in drafting and legalizing prenuptial agreements. By strengthening the position of women in such vulnerable legal circumstances, the state can fulfill its constitutional mandate to protect the rights of its citizens.